ANALISIS UNSUR-UNSUR STUKTUR BATIN BEBERAPA PUISI DALAM ANTOLOGI PUISI "SUARA PEREBUT KEMENANGAN" - YANI SURYANI (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2021)
In the research here, the inner structural elements of several poems in the anathology poem Surakarta-Central Java, each has been examined "Mendesak Bung Karno" by Vania Mogsay, "Clawing Belukar Sukar" by Wisnu Permadi, "Surat dari Ajeng" by M.Iqbal Hasibuan, and "Indigenous Tragedy" by Gista Siti Nurjanah. The inner structural elements contained in poetry consist of themes, tones, feelings and commissions. As a theoretical basis is Meinugen by Richards, quoted by Djojosuroto. To be able to analyze these poems, descriptive methods and inner approaches need to be applied. In conclusion in this research, it can be said that the theme of the four poems, here with this: "Urgent Bung Karno" by Vania Mogsay dealing with social life in Indonesia; During the colonial period, he dealt with the gripping, sad, and heartbreaking situation and was followed by a poem entitled "Clawing Hard Shrubs" by Wisnu Permadi that dealt with social life in Indonesia; During the revolution, M.Iqbal Hasibuan's poem "Surat dari Ajeng" dealt with the forty-sixth year with a hopeful, sad, and simple situation, and finally continued with a poem entitled "Indigenous Tragedy" by Gista Siti Nurjanah that dealt with a situation of anger, sadness, and deep sorrow. Discussion on the tone in these four poems is presenting ; the first is a complaint on the situation of the hero Bung Karno, where the colonial period in Indonesia; the second is the grievance of the revolutionary situation, where the hardest time in Indonesia; the third is in the forty-sixth year situation, where the motherland sews red and white flags. The interpregation contained in the feelings of these four poems is presenting: first describing a life full of struggles, tears, and fears; the second describes the situation in Indonesia, which was stranded in times of difficulty during the colonial period with pain; the third describes the struggle of motherland in the colonial period who at that time meritoriously made the red and white flag of Indonesia; the fourth depicts the sadness of the colonial era with traces of the relics of the invaders. At interprection on the fourth poetry mission he can present because, the first performance: You must have the fighting spirit of Bung Karno who became the hero of Indonesia; second show: You must have a high spirit to be like the souls of the revolution; the third describes the spirit of mother earth, in the life of women should also be able to be tough women fighting for Indonesia in the slightest; the fourth describes that your life should appreciate the traces of its ancestors or relics during the colonial era. Key words: investigation, interprecation, social life